Pola Pergantian dan Tipe Kepemimpinan Raja di Kerajaan Sunda (Suatu Telaah Pendahuluan) - W. Anwar Falah (Berkala Arkeologi, 1994)
This article describes a study of monarchy changing pattern and type of leadership in the Kingdom of Sunda. Sunda as an ancient kingdom in West Java from the beginning of 8th CE until the end of 16th CE, is presumably having received historical recognition in connection with the historiography of ancient kingdoms in Indonesia. While the name Pajajaran or Pakuan Pajajaran, was originally thought to be the name of a kingdom, it’s interpretation has changed as the capital of the Sunda Kingdom. Through the interpretation of existing textual sources, which include a number of inscriptions, foreign records (Chinese, Portuguese), as well as ancient local texts, it is known that the capital of Kingdom of Sunda throughout its history has experienced several shifting.